Molecular typing and in vitro antifungal susceptibility of Cryptococcus spp from patients in Midwest Brazil - Olivia Cometti Favalessa; Daphine Ariadne Jesus de Paula; Valeria Dutra; Luciano Nakazato; Tomoko Tadano; Marcia dos Santos Lazera; Bodo Wanke; Luciana Trilles; Maria Walderez Szeszs; Dayane Silva; Rosane Christine Hahn (Journal of Infection in Developing Countries)
Introduction: Cryptococcosis is a systemic fungal infection that affects humans and animals, mainly due to Cryptococcus neoformans and Cryptococcus gattii. Following the epidemic of acquired immunodeficiency syndrome (AIDS), fungal infections by C. neoformans have become more common among immunocompromised patients. Cryptococcus gattii has primarily been isolated as a primary pathogen in healthy hosts and occurs endemically in northern and northeastern Brazil. We to perform genotypic characterization and determine the in vitro susceptibility profile to antifungal drugs of the Cryptococcus species complex isolated from HIV-positive and HIV-negative patients attended at university hospitals in Cuiabá, MT, in the Midwestern region of Brazil. Methodology: Micromorphological features, chemotyping with canavanine-glycine-bromothymol blue (CGB) agar and genotyping by URA5-RFLP were used to identify the species. The antifungal drugs tested were amphotericin B, fluconazole, flucytosine, itraconazole and voriconazole. Minimum inhibitory concentrations (MICs) were determined according to the CLSI methodology M27-A3. Results: Analysis of samples yelded C. neoformans AFLP1/VNI (17/27, 63.0%) and C. gattii AFLP6/VGII (10/27, 37.0%). The MICs ranges for the antifungal drugs were: amphotericin B (0.5-1 mg/L), fluconazole (1-16 mg/L), flucytosine (1-16 mg/L), itraconazole (0.25-0.12 mg/L) and voriconazole (0.06-0.5 mg/L). Isolates of C. neoformans AFLP1/VNI were predominant in patients with HIV/AIDS, and C. gattii VGII in HIV-negative patients. The genotypes identified were susceptible to the antifungal drugs tested. Conclusion: It is worth emphasizing that AFLP6/VGII is a predominant genotype affecting HIV-negative individuals in Cuiabá. These findings serve as a guide concerning the molecular epidemiology of C. neoformans and C. gattii in the State of Mato Grosso.